THE EFFECT OF WORD OF MOUTH COMMUNICATION ON STUDENTS INTEREST IN VISITING MADASARI TOURISM IN PANGANDARAN - IKHSAN FUADY; HADI SUPRAPTO ARIFIN; FIRYALIA GANI SUSILA; SANIYA MASITA RINI; VIRIANA AULIA KHADIJAH (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
Madasari Beach is a beach that has potential and exotic. Promotional activities undertaken by local governments have not had an enormous impact on the number of visitors. One form of tourism promotion communication activities with word of mouth in increasing tourist interest is visiting Madasari Beach. This study aims to determine the effectiveness of the influence of the credibility of the word of mouth contribution to the interest of students visiting Madsari attractions. The study results revealed that students' interest to demonstrate to Madasari Beach was relatively high. Meanwhile, the factors that influence the effectiveness of Madasari beach tourism promotion with WOM are the message characteristic factors, in this case, the message quality. As for the credibility factor, the source has no real influence on the interest in visiting Madasari Beach.